Molecular Manipulation of the miR396 and miR399 Expression Modules Alters the Response of Arabidopsis thaliana to Phosphate Stress - Joseph L. Pegler; Duc Quan Nguyen; Jackson M. J. Oultram; Christopher P. L. Grof; Andrew L. Eamens (Plants, 2021)
In plant cells, the molecular and metabolic processes of nucleic acid synthesis, phospholipid production, coenzyme activation and the generation of the vast amount of chemical energy required to drive these processes relies on an adequate supply of the essential macronutrient, phosphorous (P). The requirement of an appropriate level of P in plant cells is evidenced by the intricately linked molecular mechanisms of P sensing, signaling and transport. One such mechanism is the posttranscriptional regulation of the P response pathway by the highly conserved plant microRNA (miRNA), miR399. In addition to miR399, numerous other plant miRNAs are also required to respond to environmental stress, including miR396. Here, we exposed Arabidopsis thaliana (Arabidopsis) transformant lines which harbor molecular modifications to the miR396 and miR399 expression modules to phosphate (PO4) starvation. We show that molecular alteration of either miR396 or miR399 abundance afforded the Arabidopsis transformant lines different degrees of tolerance to PO4 starvation. Furthermore, RT-qPCR assessment of PO4-starved miR396 and miR399 transformants revealed that the tolerance displayed by these plant lines to this form of abiotic stress most likely stemmed from the altered expression of the target genes of these two miRNAs. Therefore, this study forms an early step towards the future development of molecularly modified plant lines which possess a degree of tolerance to growth in a PO4 deficient environment.